ANALYSIS OF EMPLOYEE WORKPLACE HEALTH PROGRAMS AT RSUD DR. M.M. DUNDA LIMBOTO, GORONTALO REGENCY - Yunus, Nur Fauzia; Malaha, Adnan; Warastuti, Rita Amini (Jurnal Ilmiah dr. Aloei Saboe, 2024)
This study aims to examine the efforts made by RSUD Dr. M.M. Dunda in implementing employee health programs in accordance with Minister of Health Regulation Number 66 of 2016 on Hospital Occupational Safety and Health, as well as the challenges faced in this implementation. The research employs a qualitative descriptive approach, involving five informants. Data collection was conducted through interviews, utilizing source triangulation for data validity. The findings indicate that the occupational health efforts at RSUD Dr. M.M. Dunda Limboto include promotional programs such as extra fooding, physical fitness initiatives, recreational activities, and the provision of breastfeeding corners. Preventive programs encompass health check-ups for radiology staff, medical surveillance, workplace environmental monitoring, and health monitoring. Curative programs involve employee treatment, management of work-related illnesses, handling of occupational accidents, and post-exposure management. Additionally, several programs have yet to be implemented, including the establishment of a clean and healthy canteen, specialized mental health services for employees, comprehensive health assessments, widespread vaccination for employees, and medical rehabilitation along with a return-to-work program, which have not been initiated due to the absence of cases requiring rehabilitation